A review of void and gas bubble superlattices self-organization under irradiation - Zhang, Yongfeng (Frontiers in Nuclear Engineering, 2023)
Irradiation by high-energy particles has been well known as a destructive force that "damages" crystalline materials by creating lattice defects. One surprising outcome from irradiation is the self-organization of void superlattices and gas bubble superlattices in various materials under irradiation. While these superlattices exhibit crystal structures that mimic atomic lattices, their self-organization takes place in far-from-equilibrium environment. A thermodynamic driving force that entails ordering is either absent or yet to be identified. In the past few decades, extensive research efforts have been made to generate such superlattices and to discern their formation mechanisms. While a consensus is yet to reach, these studies have substantially enriched our understanding on defect evolution and self-organization under irradiation. Appending previous reviews that are mostly done two decades ago, this article presents a comprehensive review of new experimental, theoretical, and simulational studies of void and gas bubble superlattices in the past two decades. An in-depth discussion on the formation mechanisms and their implications on superlattice properties is provided for the purpose of encouraging future studies.